Maternal diet in pregnancy and acute leukemia in infants: a case-control study in Mexico City - Pérez-Saldivar, María Luisa; Flores-García, M. Karen; Núñez-Villegas, Nancy; Fajardo-Gutiérrez, Arturo; Medina-Sanson, Aurora; Jiménez-Hernández, Elva; Martín-Trejo, Jorge Alfonso; López-Santiago, Norma; Peñaloza-González, José Gabriel; Cortés-Herrera, Beatriz; Merino-Pasaye, Laura Elizabeth; Amador-Sánchez, Raquel; et al. (Frontiers in Oncology, 2024)
Epidemiological studies around the world on acute leukemia (AL) and risk factors in infants are scarce. Infant AL has been proposed to originate in utero, which facilitates its study by establishing a short exposure time in pregnant women to environmental and dietary factors that could contribute to the risk of or protection against leukemia. We hypothesized that maternal diet during pregnancy may be an important factor involved in AL in offspring. Methods: We conducted a hospital-based case-control study from 2010 to 2019 on maternal diet during pregnancy in nine highspecialty public hospitals of different health institutions that diagnose and offer treatment to children with AL in Mexico City. Cases (n=109) were children ≤24 months of age with de novo diagnosis of AL, and controls (n=252) were children obtained in hospitals from second-level medical care matched for age, sex, and health institution. Maternal diet during pregnancy was obtained by a semiquantitative food frequency questionnaire. Unconditional logistic regression models were used to assess the association between food groups and infant AL. Potential confounders were assessed by constructing directed acyclic graphs (DAGs) with Dagitty software in which adjusted options were identified for the construction of unconditional logistic regression models. Results: Cases were slightly predominantly female (52.3%). The years of education of the mother in cases and controls was 0-9 on average, and those who reported smoking cigarettes and consuming alcohol during pregnancy did so at a low frequency. Regarding the mother's diet, the main findings were that the consumption of allium vegetables during pregnancy was inversely associated with AL for medium and high consumption (OR=0.26, 95% CI 0.14-0.46; P-trend< 0.001). In contrast, the high consumption of high-fat dairy products had a positive association with AL (OR=2.37, 95% CI 1.30-4.34; P-trend<0.001). No association was found between consumption of topoisomerase II inhibitor foods during pregnancy and AL. Conclusion: The results suggest that maternal intake during pregnancy of allium vegetables, specifically garlic, is inversely associated with the development of AL in children ≤24 months old. On the other hand, consumption of high-fat dairy products is positively associated with AL in children ≤24 months old.